EXPLORING THE SYNERGY OF SOCIAL SERVICESCAPE AND PHYSICAL ENVIRONMENT IN ENHANCING GUEST REVISITATION IN RURAL B&B ACCOMMODATIONS - Yang, Ai-Shih (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Purpose: This study investigates how the social servicescape and physical environment interact to drive guest loyalty in rural B&Bs, focusing on the heritage-rich context of Lukang, Taiwan. Moving beyond traditional lodging evaluations, the research seeks to clarify how the synergy between human interaction and spatial authenticity sustains the competitive edge of rural hospitality. Methodology: Data were gathered from 186 B&B guests using a self-administered survey. To ensure the internal consistency of our adapted scales, Cronbach’s alpha was calculated, with all constructs exceeding the 0.70 threshold. Given the unique cultural setting of Lukang, an Exploratory Factor Analysis (EFA) using Principal Component Analysis with Varimax rotation was performed to validate the underlying dimensions. The study then utilized multiple regression analysis in SPSS to test the predictive power of these factors on revisit intentions. Findings: The regression model yielded an R2 value of 0.35, indicating that social servicescape and physical environment account for 35% of the variance in revisit intention (p < 0.001). While interpersonal interaction (β= 0.52) and safety-centered design (β= 0.42) emerged as the primary drivers, secondary factors such as cultural aesthetics and engaging leisure activities also contributed significantly to the model. These results highlight that for rural B&Bs, success is anchored in a blend of "human warmth" and a physically secure, culturally resonant environment. Conclusion: This study shifts the analytical focus from standardized urban luxury toward the intimate, community-based scale of rural micro-hospitality. Our findings reveal that competitive advantage in this sector stems from a specialized synergy: the fusion of personal host–guest hospitality with a secure, culturally authentic environment. This reframes revisit intention not as a routine transaction, but as a meaningful gesture of cultural belonging. Practically, the results suggest that B&B operators should prioritize heritage storytelling and spatial integrity over generic luxury. By doing so, they can transform service encounters into lasting emotional bonds, ultimately fostering more resilient and sustainable rural tourism development.